PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN NEXTGROW BARBERSHOP DI DESA PANDEAN KECAMATAN DURENAN KABUPATEN TRENGGALEK - Suja’i, Imam Sukwatus; Fikri Hasbian Wafa (Program Studi Akuntansi IKOPIN, 2022)
The purpose of this study was to determine whether service quality has a positive and significant impact on customer satisfaction Nextgrow Barbershop in Pan-dean Village, Durenan District, Trenggalek Regency. The type of research used is quantitative with an associative approach. The results of this study are: (a). There is a partial influence between the independent variable service quality (X) on customer satisfaction (Y), namely t hitung 5.996 > t tabel 1.674 which means signifi-cant. Then the contribution given is 41.8% and the remaining 58.2% is influenced by other varia-bles. The conclusion is that there is a partial effect on service quality (X) on customer satisfaction (Y) Nextgrow Barbershop in Pandean Village, Durenan District, Trenggalek Regency with a contri-bution of 41.8%.